Metal-Associated Enols as Key Intermediates in Controlling Enantioselectivity in Carbene Insertion Reactions - Dodiya, Dev; Harariya, Mahesh Singh; Jindal, Garima (Synlett, 2025)
Transition-metal-catalysed asymmetric carbene insertion reactions into various X–H bonds typically suffer from poor stereoselectivity. It has been proposed that the presence of metal-free intermediates leads to erosion of selectivity. In the current account, we discuss our recent efforts to understand the mechanism and stereochemical model of Rh- and Fe-catalysed carbene insertion into indole and phenol. Our detailed DFT calculations show that all transformations adopt a common mechanism involving an enol intermediate, the further tautomerisation of which is the key stereodetermining step. To account for enantioinduction, we propose a novel metal-associated enol species that can be the key to solving the challenges in asymmetric reactions. The geometry of the metal–enol complex and the interaction between the chiral metal complex and prochiral enol play important roles in driving the reaction toward a particular stereoisomer.1 Introduction2 Rh-Catalysed Carbene Insertion into Indole3 Fe-Catalysed Indole C–H Functionalisation4 Fe-Catalysed O–H Insertion5 Conclusion
Keywords: carbene insertion; transition state modelling; density functional theory; asymmetric catalysis; metal-associated enol reactions